Anti-Disturbance State Feedback Controller Based on Disturbance Reconstruction for Underactuated Overhead Crane. Issue 2 (2020) - Zhu, Fanglai; Shan, Yu
Abstract: The paper deals with the control problems for the underactuated overhead crane system with lumped disturbance. First, two-stage state transformations are made and the system is eventually transformed into a linear-like cascade system under the transformations. In order to cope with the lumped unknown inputs, an identical unknown input reconstruction method is developed and the reconstruction is based on an interval observer. And then, for the equivalent linear-like cascade system, an anti-disturbance (or anti-unknown input) state feedback controller is designed by introducing the unknown input reconstruction into the controller. Simulation results are given to show the effectiveness of our methods.